NE11 represents a new strain variant class of potato virus Y - Lorenzen, J.H.; Martin, D.; Nolte, P.; Pasche, J. S.; Gudmestad, N.C. (Springer, 2008)
This report describes the characterization by whole-genome sequencing of four PVY isolates with unique combinations of molecular and symptomatic characteristics. Three of these four isolates were of type PVYN:O (ID-1, OR-1, PN10A), including one of “type B”, which contains an extra recombination event in the 5′UTRP1 cistron; the other (NE-11) represents a novel PVY molecular genotype, previously misclassified as a PVYNA-NTN isolate. The full genome sequence of this latter isolate is unique inasmuch as it is nearly identical to that of PVYN isolates for the first 2,000 nucleotides (nts), after which it very strongly resembles PVYNA-NTN isolates for the next 600 nts. For the final 7,000 nts of its genome, NE-11 shares intermediate identity with these other two previously reported classes of PVYN genomes, except for a portion of the capsid protein region in which it resembles neither. Recombination in each of the four isolates was verified by a suite of recombination detection programs. PN10A represents the first complete sequence of a PVY strain variant of the class reported as PVYN-W (or PVYN:O) type B. Specific PCR assays for two unique regions of NE-11 are presented that will allow the identification of this strain variant by other researchers.